MENILIK PENERAPAN KEADILAN RESTORATIF DALAM MUKA PERSIDANGAN DI INDONESIA - Deva Izzatul Jannah; Vincentius Patria Setyawan (Sebelas Maret University, 2023)
This article analyzes the application of restorative justice before the trial based on the study of decision number 63/Pid. B/2021/PN Skm. The purpose of this article is to find out the basic considerations of judges in deciding cases with the application of retorative justice as an alternative solution to crime based on the study of decision number 63/Pid. B/2021/PN Skm. This article is a normative legal research with a prescriptive nature and uses primary legal materials and secondary legal materials. The technique for collecting legal materials is to use a literature study with a case approach. The analysis technique used is the syllogism method using a deductive mindset. The results of the study show that restorative justice has been implemented during the trial examination. The Suka Makmue district court judge’s decision has an element of legal certainty by implementing and adhering to legal values and a sense of justice that lives in society. The judge's decision also reflects a sense of justice and expediency, it is said that because all parties involved, both the accused, the victim, and the community can feel a sense of peace as in the same as condition before which is like the principle emphasized by restorative justice, by prioritizing the recovery of victims, the accused and the public.Keywords : Basic Considerations of the Judges; Restorative Justice; The crime of presecution